O Caldeirão da Santa Cruz do Deserto : diálogos entre literatura, história e memória - Barros, Aretha Ludmilla Pacheco Lira (2012)
This work will take as subject Caldeirão, a Claudio Aguiar s novel, for establishing the dialogues built between Literature, History and Memory. The historic nature of the novel is clear, in particular, due to the coincidence between the Caldeirão reports and the records about the event. Evident concern in the novel, of particular importance in this research, is to rescue the Caldeirão massacre s memory by Ceará public force, and claim their history right. Caldeirão is proposed, as Claudio Aguiar said clearly, tell the vanquished story, a history version that has been omitted. We ll analyze how literature has transformed into fiction a real, event using memory as the main tool. Sertão was the stage where the story takes place in the novel and where the historical event of Caldeirão s massacre happened. Therefore, we coursed Sertão by some names that brought valid contributions to that subject, as Albertina Vicentini and Janaína Amado. For the analysis base, we opted for less traditional History and Literature concepts. About the proximities between Literature and History, we had useful discussions and considerations made by Hayden White, Jorge Luis Borges, Roger Chartier, Antonio Candido and Michel de Certau. Memory and its relation to History and Literature was a key to achieve our goal in this work. We consider memory as a way to read the past being positioned at the present time. We observed and analyzed the Caldeirão s community memories, their version of that history. How the massacre occurred was seen and reported by the community as a group. The main theorists used in this discussion were: Jacques Le Goff, Walter Benjamin, Jean-Marie Gagnebin, Maurice Halbwachs and Jean-Pierre Rioux. It will be part of the discussion the limits between these disciplines, to what extent are similar and where they re fork.